Increased capacity in industrial equipment - Esteves, I. P. (2023)
This article discusses the application of continuous improvement tools in an aeronautical company. The main goals are to enhance equipment availability and efficiency, leading to improved Overall Equipment Effectiveness and reduced energy costs. The focus is optimizing specific equipment with lower productivity due to limited data and documentation. The process at different workstations is analyzed, and data is collected to apply lean tools, aiming to increase efficiency by 10% and optimize the equipment's productive capacity by 20%. The article explores the fundamentals of lean, originating from the Toyota Production System, which seeks to eliminate seven types of waste. Several lean tools such as Single Minute Exchange of Die, 5S, and Standard Work are utilized. Additionally, kaizen practices like cross-functional teams, decentralized responsibilities, the pull system, and Just-in-Time are employed to complement Lean Manufacturing. The implementation process follows the Plan-Do-Check-Act methodology, supported by the Hoshin Kanri methodology, allowing for the proper sequencing of actions and validation of achievements. Furthermore, the article touches upon the evolution of the aeronautical industry and its relationship with lean practices to establish relevant correlations. Through the application of these methods, it was considered, based on the data obtained in the initial diagnosis, an increase of 17%, 55% and 31% in the efficiency of setups in autoclaves, computerized numerical control machines and ultrasound, respectively, which in all exceeded the goal of 10%. As for the increase in equipment availability, relevant results were also obtained compared to the 20% target, having reduced about 45h/year in autoclaves in two cycles along with a gain of 19% in the occupancy of the surtec.